2022
DOI: 10.31557/apjcp.2022.23.9.3173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overall Survival between Transarterial Chemoembolization and Best Supportive Care in Intermediate- Stage Hepatocellular Carcinoma

Abstract: Objective:The Thailand management guideline allows the use of transarterial chemoembolization (TACE) for the treatment of intermediate-stage hepatocellular carcinoma (HCC) in patients with decompensated cirrhosis, whereas other guidelines do not. The aim of this study was to compare the overall survival between TACE and the best supportive care (BSC) in HCC patients with Child-Pugh score 5-8 cirrhosis and in subgroups with compensated cirrhosis (Child-Pugh score 5-6) and early decompensated cirrhosis (Child-Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…There are many studies that investigated TACE as a treatment for HCC in different settings. For example, Kong et al [29] and Akarapatima et al [30] found that TACE significantly improves the survival time of HCC patients compared to the best supportive care. In our study the best survival times were reported in patients treated neoadjuvantly with TACE, followed by other treatments including ablation and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that investigated TACE as a treatment for HCC in different settings. For example, Kong et al [29] and Akarapatima et al [30] found that TACE significantly improves the survival time of HCC patients compared to the best supportive care. In our study the best survival times were reported in patients treated neoadjuvantly with TACE, followed by other treatments including ablation and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Betroffenen, die für einen chirurgischen Eingriff oder eine RFA nicht infrage kommen oder diese ablehnen, stellt die Wahl der optimalen Behandlung eine große Herausforderung dar. Die transarterielle Chemoembolisation (TACE) ist zwar als lokale Behandlungsoption für inoperable HCC etabliert, doch die Verbesserung der onkologischen Endpunkte im Vergleich zu einer rein supportiven Therapie bleibt moderat [ 1 ]. Vielversprechende Ergebnisse konnten mit der stereotaktischen Strahlentherapie (SBRT) bei inoperablem oder rezidivierendem HCC erreicht werden [ 2 , 7 , 8 ].…”
Section: Hintergrund Der Arbeitunclassified
“…Southeast Asia exhibits distinctive epidemiological patterns regarding the frequency of HCC in HBV patients. This variation is influenced by several variables, such as virus genotypes, host immune responses, environmental conditions, and dietary habits [5][6][7]. Designing efficient prevention and control methods suited to the region's demands requires understanding the complex nature of HCC prevalence and unravelling the underlying mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%